2020
DOI: 10.1021/acsabm.0c00521
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Phospholipid Core for Mucin Hydrogel Penetration and Mucosal Cell Uptake of Maltodextrin Nanoparticles

Abstract: Nanoparticles (NPs) used as mucosal antigen delivery systems are a promising way to vaccinate. However, NPs have to cross the mucus gel and penetrate into mucosal cells to deliver antigens, and a mismatch exists between mucopenetrating NPs, rarely able to interact with cells, and NPs designed to deliver antigens into cells, but often described as mucoadhesives. Here, we compared the ability of cationic maltodextrin-based NPs, either without (NP+) or with an anionic phospholipid core (NPL), to interact with muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Moreover, mucus production is increased in IBD, requiring nanoparticles that can penetrate and diffuse through the mucus, which is the case for NPL ( Murgia et al, 2018 ). Hence, the NPL combine three potential advantages for drug delivery in the context of IBD: (i) NPL are muco-penetrating nanocarriers, thanks to their size bellow 100 nm (here 65 nm, Table 1 ) and their phospholipid core ( Fasquelle et al, 2020 ); (ii) they quickly interact and penetrate cells, due to their highly cationic surface charge (here +35 mV) ( Le et al, 2018 ); (iii) they were proved to associate and deliver hydrophobic drugs ( Kroubi et al, 2010 ). They can also protect a drug from oxidation, as shown for the anti-parasitic diminazene ( Kroubi et al, 2010 ), which is a particular advantage when using curcumin ( Betbeder et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mucus production is increased in IBD, requiring nanoparticles that can penetrate and diffuse through the mucus, which is the case for NPL ( Murgia et al, 2018 ). Hence, the NPL combine three potential advantages for drug delivery in the context of IBD: (i) NPL are muco-penetrating nanocarriers, thanks to their size bellow 100 nm (here 65 nm, Table 1 ) and their phospholipid core ( Fasquelle et al, 2020 ); (ii) they quickly interact and penetrate cells, due to their highly cationic surface charge (here +35 mV) ( Le et al, 2018 ); (iii) they were proved to associate and deliver hydrophobic drugs ( Kroubi et al, 2010 ). They can also protect a drug from oxidation, as shown for the anti-parasitic diminazene ( Kroubi et al, 2010 ), which is a particular advantage when using curcumin ( Betbeder et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, with 70% ( w / w ) of incorporated lipids, NPLs behave exactly like uncharged, neutral maltodextrin NPs, while NPs + bind strongly to the proteins. Similarly, a study carried out on respiratory tract mucus showed that the binding of NPLs to mucins decreased with increasing amounts of incorporated DPPG [ 51 ]. As a result, NPLs behave like zwitterionic NPs, despite their cationic surface charge, and are hence better vectors than NPs + for crossing the mucosal barrier [ 52 , 53 ].…”
Section: Lipidated Cationic Maltodextrin Nps For Antigen Deliverymentioning
confidence: 99%
“…Cationic reticulated maltodextrin-based nanoparticles with a phospholipid core (NPL) are porous and spherical NPs, able to be loaded with and deliver a large amount of antigen into epithelial and immune cells [23,24]. Due to their anionic lipid core, NPL penetrate the mucus after nasal administration and therefore increase the antigen retention time in the nasal mucosa [25][26][27]. Accordingly, they are ideal for nasal immunization [28][29][30].…”
Section: Introductionmentioning
confidence: 99%